2018
DOI: 10.1186/s40959-018-0030-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of integrated imaging and serum biomarker profiles to identify subclinical dysfunction in pediatric cancer patients treated with anthracyclines

Abstract: Background Anthracycline induced cardiomyopathy is a major cause of mortality and morbidity among pediatric cancer survivors. It has been postulated that oxidative stress induction and inflammation may play a role in the pathogenesis of this process. Accordingly, the present study performed an assessment of biomarker profiles and functional imaging parameters focused upon potential early determinants of anthracycline induced cardiomyopathy. Methods Patients (10–22 years) were prospectively enrolled between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 66 publications
1
8
0
1
Order By: Relevance
“…Bjornstad et al were the first pediatric study to analyze strain cardiac strain from 2D-STE in adolescents with T2DM and found that compared to lean and to obese controls, adolescents with T2D had significantly lower CS [27]. Our results showcase similar findings as adolescents with dysglycemia, which included a small T2DM cohort, were observed to have a depressed CS, despite differences in study demographics, namely differences in ethnicity and a more obese cohort in our group (BMI Z = 2.49) compared to Bjornstad’s group (BMI Z = 2.01) [28, 29]. Our study thus underscores that dysglycemia attenuates unfavorable cardiac remodeling in obese adolescents, as demonstrated by changes in LS and CS.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Bjornstad et al were the first pediatric study to analyze strain cardiac strain from 2D-STE in adolescents with T2DM and found that compared to lean and to obese controls, adolescents with T2D had significantly lower CS [27]. Our results showcase similar findings as adolescents with dysglycemia, which included a small T2DM cohort, were observed to have a depressed CS, despite differences in study demographics, namely differences in ethnicity and a more obese cohort in our group (BMI Z = 2.49) compared to Bjornstad’s group (BMI Z = 2.01) [28, 29]. Our study thus underscores that dysglycemia attenuates unfavorable cardiac remodeling in obese adolescents, as demonstrated by changes in LS and CS.…”
Section: Discussionsupporting
confidence: 80%
“…Serum biomarkers of inflammation, namely adipokines and leptins, have been associated myocardial deformational change [29]. Adiponectin is an adipokine secreted by adipocytes and has been established to have a cardio protective effect, and elevated adiponectin has been associated with lower risk of myocardial infarction in men [34].…”
Section: Discussionmentioning
confidence: 99%
“…Myocyte hypertrophy (Spinale and Zile 2013; Spinale 2002; Yokoyama et al 1997), myosin heavy-chain switch(Kubota et al 1997), cardiac myocyte apoptosis (Krown et al 1996) and extracellular matrix alterations with early loss of fibrillar collagen followed by late microscopic fibrosis, contribute to adverse cardiac remodeling ultimately leading to heart failure (Liew and Dzau 2004; Kong et al 2014). In our pediatric early AIC cohort, we have identified biomarker signatures in inflammatory, structural and cell growth/viability pathways (Toro-Salazar et al 2018). cTNI and MYL3 exhibited significant treatment effects across 9 and 5 strains respectively, suggesting that cTNI was the more sensitive indicator of acute injury.…”
Section: Discussionmentioning
confidence: 99%
“…We have also demonstrated that 99m Tc-RP805 myocardial uptake strongly correlates to ex vivo MMP activity ( 5 , 7 ). Notably, several MMP isoforms that 99m Tc-RP805 detects have been shown to be upregulated in the myocardium of various animal models of AIC ( 8 , 9 ) and in the circulation of patients treated with DOX ( 10 ). Thus, it stands to reason that pharmacotherapies that modify MMP activity may hold relevance in the context of AIC, and that 99m Tc-RP805 can be used to assess changes in MMP-TIMP balance.…”
mentioning
confidence: 99%